2021
DOI: 10.3390/md19030127
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Tuna Bioactive Peptide on Dextran Sulfate Sodium-Induced Colitis in Mice

Abstract: Bioactive peptides isolated from marine organisms have shown to have potential anti-inflammatory effects. This study aimed to investigate the intestinal protection effect of low molecular peptides (Mw < 1 kDa) produced through enzymatic hydrolysis of tuna processing waste (tuna bioactive peptides (TBP)) on dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) in BALB/c mice. Here, we randomly divided twenty-four male BALB/c mice into four groups: (i) normal (untreated), (ii) DSS-induced model colitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Other researchers have also reported that it is possible to induce a mouse model of acute experimental colitis models using methods similar to those reported in this study [39,40]. A series of studies have shown that food components have favorable ameliorative effects on acute colitis [8][9][10][11][12]. We conducted the first study on the attenuation of acute experimental colitis by OE.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Other researchers have also reported that it is possible to induce a mouse model of acute experimental colitis models using methods similar to those reported in this study [39,40]. A series of studies have shown that food components have favorable ameliorative effects on acute colitis [8][9][10][11][12]. We conducted the first study on the attenuation of acute experimental colitis by OE.…”
Section: Discussionmentioning
confidence: 58%
“…These alternative therapies are of great interest because of their low side effects [7]. Among these, algal oil [8], propolis extract [9], peptides derived from tuna [10], taurine [11], and astragalin [12] have been reported to exert protective effects against experimental colitis induced by dextran sulfate sodium (DSS) in mice. Thus, the potential exists for IBD patients to have a greater variety of substances that are effective, in the form of alternative treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The pecan protein isolate (PPI) hydrolysate showed differential antioxidant activities after fractionation by ultrafiltration through cut‐off membranes with molecular weights of 10, 5, and 3 kDa, where the highest antioxidant effect was observed in the fraction containing the lowest molecular weight peptides (<3 kDa) (Hu et al ., 2018). This enhancement in biological activity can be attributed to a lower steric hindrance and a reduction in repulsion between peptides (Nwachukwu & Aluko, 2019; Sun & Udenigwe, 2020; Xiang et al ., 2021). Likewise, these low molecular weight peptides show better absorption efficiency across biological membranes than larger amino acid sequences (Xiang et al ., 2021).…”
Section: Antioxidant and Anticancer Activitiesmentioning
confidence: 99%
“…Anti-inflammatory protein products are often short, LMW peptides [ 43 , 52 , 63 ]. This is fortuitous because small peptides are more readily absorbed by the body, and this allows the possibility that the anti-inflammatory peptides may be utilized as orally administered therapeutics [ 3 , 64 ]. LMW protein products are more likely to cross the intestinal barrier intact, thus increasing the possibility that they can exert anti-inflammatory action in the body [ 34 , 48 , 65 ].…”
Section: Fish and Shellfish-derived Anti-inflammatory Protein Products: Properties And Mechanismsmentioning
confidence: 99%